Can Cancellara Really be a Flandrien? Ethno-Cultural Identity Representation Predicts Regional Exclusivity of a Historically Contested Cycling Term. Issue 1 (19th March 2018) - Van Puyenbroeck, Stef; Delheye, Pascal; Knuts, Stijn; Vander Elst, Liesbeth; Fransen, Katrien; Vanbeselaere, Norbert; Boen, Filip
In Flanders the term flandrien refers to cyclists who display a strong work ethic, great perseverance, are powerful and who perform best in adverse weather conditions. Until the 1960s, only leading cyclists originating from the province of West- and East-Flanders were considered as flandriens . After 1960, the media extended the use of this term to Belgian cyclists in general and even to international cyclists. The present study examined whether Flemish citizens agree with this generalization considering that the term flandrien still plays a highly symbolical role in the public discourse on Flemish identity. First, the main aim was to investigate whether having an ethno-cultural identity representation of the Flemish identity is positively related to perceived regional exclusivity of the term flandrien . Second, this study explored whether Flemish identification moderates this relation (i.e. this relation is only expected for high identifiers) and also predicts Flemings' regional exclusivity of the term. Results revealed that the more Flemings endorse an ethno-cultural identity representation the more they consider a flandrien as an exclusively Flemish cyclist, and the less they will include international cyclists in their consideration of a flandrien . Flemish identification did not moderate this relation but did predict the consideration of a flandrien as a Flemish cyclist. These findings indicate that the current interpretation of the historical cycling term flandrien is influenced by cultural conceptualizations of Flemish identity.